The impact of implementing Personal Software Process (PSP) on organizations / Ahmad Sabri Idris - Idris, Ahmad Sabri (Faculty of Information Technology and Quantitative Sciences, 2005)
The Personal Software Process (PSP) is a self-improvement process designed to help you control, manage and improve the way you work (Humphrey, 1995). It is a structured framework of form, guidelines and procedures for developing software. Properly used, the PSP provides the historical data you need to better make and meet commitments and it makes the routine elements of your job more predictable and more efficient. The purpose of this research is to determine the awareness on selected companies either they realize or not with the elements of PSP on their organization. So that, one staff from each company will be interview to gather this information. The interviews questions are about PSP key process areas, the elements of PSP and also form that have been introduced by Watts Humphrey in PSP where these companies use or not. The percentage will be stated base on what the researcher has found from the interview sessions.